Pengaruh Fraud Hexagon terhadap Fraudulent Financial Statement pada Perusahaan BUMN yang Terdaftar di BEI Tahun 2018-2022 - El fath, Nurul Hazimah; Setiawan, Mia Angelina (Jurnal Eksplorasi Akuntansi, 2024)
This study aimed to determine the effect of fraud hexagon on fraudulent financial statement. The research was conducted in BUMN companies listed on the Indonesia Stock Exchange with an observation period of 2018-2022. The sampling methode used was purposive sampling, while the research sample consisted of 24 companies were indexed on the IDX. The data analysis technique used is Multiple Linear Regression Analysis. The study results show pressure affects fraudulent financial statements. The Capability, Collusion, Opportunity, Rationalization, and Arrogance have no effect on the Fraudulent Financial Report.